AB0040 IMPAIRED REGULATORY T CELL FUNCTIONS IN PATIENTS WITH PSORIASIS ARTHRITIS ELIGIBLE TO SWITCH TO ANTI-IL-17 TREATMENT. (2nd June 2020) - Christoforou, T.; Almanzar, G.; Brauneiser, F.; Buschmann, N.; Feuchtenberger, M.; Schmalzing, M.; Tony, H. P.; Goebeler, M.; Prelog, M.
Abstract : Background: A dysbalance between Th17 and regulatory T cells (Treg) has been suggested for several T cell-mediated autoimmune disorders. Inhibitors of IL-17 are successfully used for treatment of psoriasis arthritis (PsA). However, so far reconstitution of Treg functions has not been studied in detail in PsA eligible for switching to anti-IL-17 treatment. Objectives: The project aims to analyze the reconstitution and maintenance of regulatory T cell (Treg) function after inhibition of inflammatory Th17-inducing pathways mediated by IL-1, IL-6, IL-17 and TNFalpha in a longitudinal manner. Methods: Therefore, Treg derived from 12 PsA patients switching to Th17 inhibition and healthy controls were phenotypically characterized by flow cytometry. Function was investigated by analysis of suppressive activity of Treg on proliferation of autologous effector T cells in vitro utilizing suppression assays. Results: First results at the time-point of switching to anti-IL-17 treatment demonstrated PsA to be an IL-17-driven T cell-mediated autoimmune disorder, as proportions of T cells with Th17 phenotype were increased in PsA compared to controls (CCR6+IL-17 + 4.9% vs. 0.8% of CD4+) and FoxP3+ Treg cells (CD25brightFoxP3 + 0.2% vs. 0.4% of CD4+) were decreased. Higher proportions of FoxP3+ T cells expressing the Th17-characteristic chemokine receptor CCR6 were found in PsA (4.8% vs. 2.7% of CD4+), as well as higher proportions of pro-apoptotic CD95-expressing FoxP3+ T cells (9.8% vs. 2.8% of CD4+). Less suppression of autologous effector T cells co-cultured with CD25+ Treg cells was found in PsA compared to controls (22.2% vs. 28.3% reduction of proliferative activity), whereas CD25- helper T cells did not contribute to the suppression of effectors in PsA and only minimally in controls. Intracellular IL-10 production in Tregs, a key cytokine of Treg-associated regulation of inflammation, was similar between PsA and controls, although a trend to lower CTLA-4 expression involved in inhibition of co-stimulation was found in PsA. Conclusion: The current results indicate a skewed T cell balance towards Th17 cells and Treg cells showing Th17-like features in samples of PsA unsuccessfully pre-treated with different biologics recommending them for a switch to a therapy with selective inhibition of IL-17. Longitudinal results regarding the reconstitution and maintenance of Treg function in those PsA patients have to be awaited. Disclosure of Interests: Timotheos Christoforou: None declared, Giovanni Almanzar Grant/research support from: Pfizer, Franziska Brauneiser: None declared, Nils Buschmann: None declared, Martin Feuchtenberger Consultant of: Abbvie, BMS, Chugai, Sanofi, Speakers bureau: Abbvie, BMS, Celgene, Chugai, Jansen-Cilag, Lilly, Pfizer, Roche, Sanofi, UCB, Marc Schmalzing Consultant of: Paid consultant for Hexal AG, Hans-Peter Tony Consultant of: AbbVie, Astra-Zeneca, BMS, Chugai, Janssen, Lilly, MSD, Novartis, Pfizer, Roche, Sanofi, Matthias Goebeler: None declared, Martina Prelog Grant/research support from: Chugai, Sobi, Novartis, Pfizer, Baxter, Consultant of: GSK, Pfizer, Novartis, MSD, Baxter, Sobi, Johnson, Speakers bureau: GSK, Pfizer, Novartis, MSD, Baxter, Sobi, Johnson